Aesthetic Autonomy and Self-Aggrandisement. (3rd October 2014) - Robson, Jon
<x content-type="archive" xml:space="preserve">Abstract</x> You're not as clever as you think you are. Nor for that matter are you as good a driver, teacher or romantic partner as you take yourself to be and, as if that wasn't bad enough, you are also considerably less popular than you have hitherto believed. Finally – and crucially for the argument of this paper – I contend that your abilities as an aesthetic judge are considerably less impressive than you take them to be. To avoid descending into name calling it's worth pointing out that such claims apply to the vast majority of people – myself, somewhat paradoxically, included.